2000
DOI: 10.1007/s004310051307
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid hemiagenesis: ultrasound screening in normal children

Abstract: This first systematic ultrasound evaluation of thyroid hemiagenesis in normal children established a prevalence of thyroid hemiagenesis of 0.2% and confirmed the female predominance and higher incidence of agenesis of the left lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 12 publications
5
83
1
2
Order By: Relevance
“…Along with age, individuals with a unilateral thyroid agenesis frequently develop compensatory hypertrophy of the contralateral thyroid tissue, thyroid nodular disease, and thyroid autoimmune disorders, which are usually not observed among children. This could explain the controversial conclusions about the benign character of this anomaly derived from the recent population-based studies in children (2,6,15). According to these studies, no abnormalities except a significantly increased level of TSH and FT 3 , combined with the presence of compensatory hypertrophy described in the first paper, were found in children with THA.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Along with age, individuals with a unilateral thyroid agenesis frequently develop compensatory hypertrophy of the contralateral thyroid tissue, thyroid nodular disease, and thyroid autoimmune disorders, which are usually not observed among children. This could explain the controversial conclusions about the benign character of this anomaly derived from the recent population-based studies in children (2,6,15). According to these studies, no abnormalities except a significantly increased level of TSH and FT 3 , combined with the presence of compensatory hypertrophy described in the first paper, were found in children with THA.…”
Section: Discussionmentioning
confidence: 94%
“…Recent population-based studies estimated the prevalence of THA for 0.2-0.025% (2,6,15,16). Agenesis, for unknown reasons, concerns the left thyroid lobe in the majority of cases, 68-80% according to different reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoplasia of an orthotopic, bilobed gland has been reported to account for at most 5% of cases and thyroid hemiagenesis for less than 0.5% (Van Vliet, 2003). As hemiagenesis is occasionally detected in asymptomatic individuals (Shabana et al, 2000;Korpal-Szczyrska et al, 2008) it could perhaps be questioned if it should really be included in the spectrum of disorders underlying CH (see below).…”
Section: Thyroid Dysgenesismentioning
confidence: 99%
“…Thyroid hemiagenesis, meaning absence of one lobe, is occasionally detected among asymptomatic individuals; prevalence figures from 0.05% (Maiorana et al, 2003;Korpal-Szczyrska et al, 2008) to 0.2% (Shabana et al, 2000) have been reported. Interestingly, hemiagenesis almost invariably affects the left lobe, suggesting a specific developmental cause rather than a stochastic mechanism.…”
Section: Clinical Features Of Thyroid Hemiagenesismentioning
confidence: 99%